FITRAH DAN PSIKOLOGI TRANSPERSONAL: MENJAWAB TANTANGAN PENDIDIKAN ISLAM DI ERA DIGITAL - Muminatus Fitriati Firdaus; Henny Regina Salve; Sulhatul Habibah (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2026)
The rapid development of digital technology has brought various challenges, such as fragmented attention, digital social pressure, and identity struggles related to the meaning of life, resulting in changes to students’ psychological and social environments. These dynamics, within the context of Islamic education, require an approach that addresses not only students’ cognitive development but also their spiritual dimensions and consciousness. This article examines the integration of the concept of fitrah in Islam and transpersonal psychology as a conceptual framework to address contemporary challenges in Islamic education during the digital era. This study used a systematic literature review approach, examining relevant studies on fitrah, transpersonal psychology, fitrah and transpersonal psychology, and digital era. These findings yield a conceptual model of integration between Fitrah and Transpersonal Psychology to address the challenges of the digital era within the context of Islamic education, comprising the digital context, fitrah, self-awareness, transpersonal consciousness, meaning-making, human transformation, and holistic Islamic education. Education in Islam is understood as a holistic process of human transformation, grounded in fitrah and transpersonal consciousness, thereby fostering students' ability to address the challenges of digitalization.